PELAKSANAAN PROMOSI OBJEK WISATA GOA HUTA SIKAPIR DI KABUPATEN ROKAN HULU - Sakdiah, Halimatun; Arief, Andi M. Rifian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Promotion is part of marketing, namely to encourage, persuade, inform, explain, and their recalling a produk both goods and services. With the implementation of the promotion is done in an attraction make the object easier to be know and recognized by potential visitors, so visitor are easy to reach attractions.This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 41 respondents, who were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With sub-variables on promotion (H.Hamdani, 2012) is divided into the advertising,, Sales Promotion, Personal Selling, Public Relation,Word of Mounth and Direct Marketing.From the results of research conducted in the field of research on the Promotion in Atraction Cave Huta Sikapir District Rokan Hulu Riau Province, with the theory of the fundamentals of marketing manajement that is divided in six sub-variables, namely, the advertising, personal selling, sales promotion, public relationword of mounth dan direct marketing , it results in the field can namely Promotion in Atraction Cave Huta Sikapir District Rokan Hulu Riau Province included in the category of pretty good.Keywords: Promotion, Advertising, Personal Selling, Sales Promotion and Public Relation.